Textul... ca mască (fragment din lecția publică): Carolina Dodu-Savca - admin, admin (BIBLIOPOLIS, 2022)
The generic "Mask is EU" is a complex, multi-angle challenge and multi-faceted, at the same time interesting, difficult and mysterious. "Mask in literature" and / or / versus "Text as a mask". What does it mean? this slogan? He is a tenderer, he assumes everything, especially today. What compels us? It forces us, I would say, not to keep our distance compared to the literary text. So, in literature, we can blatantly violate the rules of real life, because life also violates them. And real and virtual, and immediately and imaginary, the mask co-relates to the different truth, even controversial.